First case of drug eruption due to ipragliflozin: Case report and review of the literature. (31st May 2016) - Saito‐Sasaki, Natsuko; Sawada, Yu; Nishio, Daisuke; Nakamura, Motonobu
Abstract: Ipragliflozin is a new drug for the treatment of diabetes mellitus. Its action of sodium‐glucose cotransporter 2 (SGLT2) inhibition induces glucosuria and decreases blood glucose levels. We report the first case of ipragliflozin‐related eczematous drug eruption and a review of the past literature on drug eruptions caused by SGLT2 inhibitors.